Penerapan Asas Demokrasi Terkait Pemekaran Provinsi Di Wilayah Papua - Yohana Sekar Pawening; Wicipto Setiadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Regarding the principle of democracy, it can be applied to the process of expanding the province, especially for large areas. Especially for the Papua region, which from the time of independence until 2022. The division of the Papua Province into several provinces is a central government policy in order to accelerate the development of indigenous peoples in the Land of Papua. Papua Province, the easternmost region of the Unitary State of the Republic of Indonesia. On July 25, 2022, three laws were passed related to the establishment of a new province in Papua, namely Law Number 14 of 2022 concerning the Establishment of South Papua Province, Law Number 15 of 2022 concerning the Establishment of Central Papua Province, and Law Number 16 of 2022 concerning the Establishment of Papua Province Mountains. The ministries/institutions, the Papua Provincial Government and the entire community need to provide support for the running of the government in the three newly formed provinces for the realization of the welfare and progress of the people in the three provinces and the entire province of Papua.